PENGARUH PEMBERIAN YOGHURT BUAH DELIMA (Punica granatum) TERHADAP GAMBARAN HISTOPATOLOGI KOLON TIKUS PUTIH (Rattus norvegicus) YANG DIINDUKSI 1,2-dimethilhidrazine (DMH) - Kurniawati, Ajeng Dyah; Najah, Sabila; Widyawati, Ana; Latifasari, Nurul; Zunita, Evia (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
This study aimed to discuss the effect of yogurt fortified with pomegranate-fortified yoghurt, containing key antioxidant compounds such as anthocyanins, on male Wistar rats (Rattus norvegicus) induced by 1,2-dimethylhydrazine (DMH), a carcinogenic compound for colon cancer. The first stage of this study was testing antioxidant activity in various methods of making yogurt. A colon cancer rat group was induced with DMH with a dose of 20 mg/kg/body weight for 5 weeks by subcutaneous injection once a week. Induction of 1.2 DMH in experimental animals was carried out for 5 weeks, while the induction of pomegranate yogurt was carried out using oral induction every day for 4 weeks. The highest antioxidant activity was obtained from yogurt made by mixing plain yogurt and fermented pomegranate juice, where the proportion of pomegranate juice was greater, resulting in a percentage inhibition value of 77.96%. Giving pomegranate yogurt for 4 weeks was able to improve the histopathological picture of rats induced by 1.2 DMH. The best improvement in the histopathological in the colon of rats induced by 1.2 DMH was achieved by the P3 treatment group, where the proportion of pomegranate was greater when compared to plain yogurt.